0294 A Goddess of the Night, a Roman Gem, and the Bachstitz Gallery - Claire L. Lyons (RIHA Journal, 2023)
Two Roman objects in the J. Paul Getty Museum, a bronze statuette of the moon goddess Luna and a cornelian gem, were among the handful of classical antiquities acquired for Adolf Hitler’s unrealized "Führermuseum" in Linz. This study presents new provenance research that tracks their itinerary from European private collections to the gallery of Kurt Walter Bachstitz, a prominent Jewish art dealer active in The Hague between the 1920s and the 1940s. His precarious personal and business relationships with German art agents expose how ordinary commerce was entangled with coerced sales in the Nazi-occupied Netherlands. In 2015, the ownership of works that changed hands on wartime art markets informed the Dutch Restitution Committee’s recommendation to return the gem to Bachstitz’s heirs but to reject their claim on the statuette. Having passed through several collections following their restitution after World War II, the two objects were reunited at the Getty in 2017.